Risk Factors of Non-Classic Radiation-Induced Liver Disease (ncRILD) After Intensity-Modulated Radiotherapy in Hepatocellular Carcinoma - Du YQ; Tao SP; Li JX; Zhao YN (Cancer Management and Research)
You-Qin Du,1,2 Su-Ping Tao,3 Jian-Xu Li,1 Yin-Nong Zhao2 1Department of Radiation Oncology, Guangxi Medical University Cancer Hospital, Nanning, Guangxi, 530021, People’s Republic of China; 2Department of Hepatobiliary Surgery, Guangxi Medical University Cancer Hospital, Nanning, Guangxi, 530021, People’s Republic of China; 3Department of Oncology, Guiping People’s Hospital, Guiping, People’s Republic of ChinaCorrespondence: Yin-Nong Zhao, Department of Hepatobiliary Surgery, Guangxi Medical University Cancer Hospital, Nanning, Guangxi, 530021, People’s Republic of China, Tel +86 18977783542, Email zhaoyinnong@gxmu.edu.cnPurpose: This study aimed to identify independent risk factors for non-classic radiation-induced liver disease (ncRILD) in hepatocellular carcinoma (HCC) patients treated with intensity-modulated radiation therapy (IMRT) and to construct a predictive nomogram.Patients and Methods: We retrospectively analyzed 177 primary HCC patients treated with IMRT between 2013 and 2021. Univariate and multivariate analyses were conducted to identify risk factors for ncRILD. A nomogram was developed based on significant variables. Dosimetric parameters were also assessed across different fractionation doses.Results: Multivariate analysis identified tumor number ≥ 2, mean liver dose ≥ 1371.4 cGy, and normal liver volume < 700 mL as independent risk factors for ncRILD. A nomogram was established using logistic regression. In patients receiving ≥ 4 Gy per fraction, ncRILD was significantly associated with Vs5–Vs40 (p < 0.05), but not with V5–V40. No such associations were found for 2 Gy and 3 Gy groups.Conclusion: Patients with multifocal tumor, lower normal liver volume and higher mean liver dose are at increased risk of developing radiation-induced liver injury. These findings suggest that dosimetric parameters, especially at higher fraction doses, may play a critical role in the occurrence of ncRILD.Keywords: hepatocellular carcinoma, ncRILD, IMRT, liver toxicity, child-Pugh score